Revisión de las cactáceas argentinas, II : Pterocactus - Castellanos, A. (1961)
The author continues the revision of the Argentine Cactaceae and elaborates in this paper the revision of the Pterocactus Kind. As its northern limit he recognizes the locality of Amaicha (Tucumán), and as the southern - that of San Julián (Chubut). To the Known species - only four, according to him - he adds a fifth: Pterocactus araucanus nv. sp., apparently endemic in Chubut and Neuquén.